2016
DOI: 10.1016/j.ejr.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular function and aortic elastic properties in patients with Behçet’s disease using conventional and tissue Doppler echocardiography

Abstract: Background: Behc¸et disease (BD) is a multisystemic, chronic inflammatory disorder of unknown etiology with diffuse clinical manifestations including the cardiovascular system.Aim of the work: To assess left ventricular (LV) function and thoracic aorta elastic properties in BD patients using Doppler echocardiography and to correlate echocardiographic findings with disease activity.Patients and methods: The LV functions and thoracic aorta elastic properties were assessed in 30 BD patients and 30 controls using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Right after the ventricles filled with the oxygenated or deoxygenated blood, the ventricles pump the blood into the large arteries to be transferred to the whole body and to the lung for the deoxygenated blood exchange. Number of studies reported [1], [2] the left ventricle is located at the bottom left portion of the heart below the left atrium, separated by the mitral valve. Various conditions may affect the left ventricle and interfere with its proper functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Right after the ventricles filled with the oxygenated or deoxygenated blood, the ventricles pump the blood into the large arteries to be transferred to the whole body and to the lung for the deoxygenated blood exchange. Number of studies reported [1], [2] the left ventricle is located at the bottom left portion of the heart below the left atrium, separated by the mitral valve. Various conditions may affect the left ventricle and interfere with its proper functioning.…”
Section: Introductionmentioning
confidence: 99%